Parallel Problem Solving from Nature, PPSN XI 11th International Conference, Krakw̤, Poland, September 11-15, 2010, Proceedings, Part I - Schaefer, Robert.; Cotta, Carlos.; KoBodziej, Joanna.; Rudolph, G<U+00fc>nter. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the 11th International Conference on Parallel Problem Solving from Nature - PPSN XI, held in Krakw̤, Poland, in September 2010. The 131 revised full papers were carefully reviewed and selected from 232 submissions. The conference covers a wide range of topics, from evolutionary computation to swarm intelligence, from bio-inspired computing to real world applications. Machine learning and mathematical games supported by evolutionary algorithms as well as memetic, agent-oriented systems are also represented.